2018
DOI: 10.1038/s41598-018-26897-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics insights into the genetic regulation of root apical meristem exhaustion and determinate primary root growth in Pachycereus pringlei (Cactaceae)

Abstract: Many Cactaceae species exhibit determinate growth of the primary root as a consequence of root apical meristem (RAM) exhaustion. The genetic regulation of this growth pattern is unknown. Here, we de novo assembled and annotated the root apex transcriptome of the Pachycereus pringlei primary root at three developmental stages, with active or exhausted RAM. The assembled transcriptome is robust and comprehensive, and was used to infer a transcriptional regulatory network of the primary root apex. Putative orthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…The termination of root growth suggests that Ceratopteris SBRs follow a determinate growth program, even in the presence of nutritional sufficiency. This is concordant with the concept of primary homorhizy indicating that, at least, the first SBR has a short time span (Schneider, 2013 terminal stage displayed a similar transcriptional profile to the differentiation zone of Arabidopsis, where genes involved stemness and proliferation are downregulated (Benesova, 2016;Gutierrez-Alanis et al, 2015;Rodriguez-Alonso et al, 2018;Rodriguez-Rodriguez et al, 2003).…”
Section: Ceratopteris Stem-borne Roots Display Growth Cessationsupporting
confidence: 75%
“…The termination of root growth suggests that Ceratopteris SBRs follow a determinate growth program, even in the presence of nutritional sufficiency. This is concordant with the concept of primary homorhizy indicating that, at least, the first SBR has a short time span (Schneider, 2013 terminal stage displayed a similar transcriptional profile to the differentiation zone of Arabidopsis, where genes involved stemness and proliferation are downregulated (Benesova, 2016;Gutierrez-Alanis et al, 2015;Rodriguez-Alonso et al, 2018;Rodriguez-Rodriguez et al, 2003).…”
Section: Ceratopteris Stem-borne Roots Display Growth Cessationsupporting
confidence: 75%
“…Root growth relies on the balance of proliferation and differentiation in root stem cells (Petricka et al, 2012). Plant root systems can be divided into three zones along the longitudinal axis; namely, the meristematic, elongation, and maturation zones (Rodriguez-Alonso et al, 2018). The most characteristic stem cells of plants are in the shoot apical meristem and root apical meristem (Sarkar et al, 2007).…”
Section: Gradient Distribution Of Ros Regulates Root Stem Cell Differmentioning
confidence: 99%
“…This positions mature xylem cells closer to the root tip, allowing rapid water uptake during spontaneous rainfall [34]. Transcriptome analysis of active and differentiated meristems of roots of the cactus Pachycereus pringlei identified orthologues of Arabidopsis developmental regulators, such as the GRAS-domain transcription cofactors SHR and SCR, as well as the transcription factor JKD, which regulate ground tissue and QC specification in Arabidopsis [35,36]. This study also revealed an upregulation of genes involved in abscisic acid (ABA) responses at the determinate stage [35].…”
Section: The Cactus Root System Is Optimized To Exploit Top-soil Watermentioning
confidence: 99%
“…Transcriptome analysis of active and differentiated meristems of roots of the cactus Pachycereus pringlei identified orthologues of Arabidopsis developmental regulators, such as the GRAS-domain transcription cofactors SHR and SCR, as well as the transcription factor JKD, which regulate ground tissue and QC specification in Arabidopsis [35,36]. This study also revealed an upregulation of genes involved in abscisic acid (ABA) responses at the determinate stage [35]. With the role of ABA in mediating the response to drought, it is plausible that cactus tolerance to drought might be mediated by an increase in ABA levels, while meristem differentiation might result from a change in hormone homeostasis and an alteration of stem cell regulatory networks.…”
Section: The Cactus Root System Is Optimized To Exploit Top-soil Watermentioning
confidence: 99%
See 1 more Smart Citation